A methodology for the local enviromental conditioning and its aplication in the disctric of Comas - Valdivia Fernández, Helga (2006)
A proposal is presented understanding the necessity of developing forms or ways of making the planning and local management of the development concept viable, starting with a focus on territory and atmosphere. A methodology proposal on the base of the territorial analysis and its antropic dynamics is presented, which we denominate methodology for the local environmental conditioning. This methodological proposal is based on the identification and classification of areas of environmental risk, applicable to diverse environments in the domestic district and provincial range. Also, the methodology proposal is applied in the district of Comas, as a way of showing its implementation in the local environment in a practical way.